Who performs neonatal hip assessment: is there a cause for concern? - James G B MacLean; Justine E A Burt; Nourah AlKandari; Donald M Campbell (BMJ Publishing Group, 2024)
Objective The UK falls behind other European countries in the early detection of developmental dysplasia of the hip (DDH) and screening strategies differ for early detection. Clinical detection of DDH is challenging and recognised to be dependent on examiner experience. No studies exist assessing the number of personnel currently involved in such assessments.Our objective was to review the current screening procedure by studying a cohort of newborn babies in one teaching hospital and assess the number of health professionals involved in neonatal hip assessment and the number of examinations undertaken during one period by each individual.Methods This was a retrospective observational study assessing all babies born consecutively over a 14-week period in 2020. Record of each initial baby check was obtained from BadgerNet. Follow-up data on ultrasound or orthopaedic outpatient referrals were obtained from clinical records.Results 1037 babies were examined by 65 individual examiners representing 9 different healthcare professional groups. The range of examinations conducted per examiner was 1-97 with a median of 5.5 examinations per person. 49% of individuals examined 5 or less babies across the 14 weeks, with 18% only performing 1 examination. Of the six babies (0.48%) treated for DDH, one was picked up on neonatal assessment.Conclusion In a system where so many examiners are involved in neonatal hip assessment, the experience is limited for most examiners. Currently high rates of late presentation of DDH are observed locally, which are in accordance with published national experience. The potential association merits further investigation.